Policy design and implementation: a quantitative evaluation and empirical study of China's rural sports policy based on the PMC index model - Baibing Chen; Baibing Chen; Qizhi Zhu; Dongfang Xie; Yaoxian Lao; Hong Li (Frontiers Media S.A., 2024)
The formulation and implementation of a rural sports policy is an important means of promoting rural sports, improving the physical wellbeing of farmers, and enhancing the cohesion of rural communities. However, introducing such a policy faces problems in the process of specific policy practices, such as poor effective implementation, a lagging implementation effect, and goal cognitive bias. How to look at the current rural sports policy implementation blockage problem and the governance of the blockage, in order to improve the level of rural sports public service, is the focus of this paper's research. On this basis, this paper selects 56 policy texts, issued from 2002 to 2023, that are highly relevant to rural sports and have high timeliness and authority from the sports policies issued in China. Also, ROST CM6 software is used to count high-frequency words; this study then draws keyword social network mapping for the visual analysis of policy preferences and selects 20 rural sports policy texts as typical samples. Finally, a policy modeling research consistency (PMC) index model is used to evaluate the texts comprehensively and quantitatively. The results show that the overall design of China's rural sports policies is relatively reasonable. However, the consistency and effectiveness of their implementation need to be improved. Twenty representative policy texts have an average PMC index score of 5.96, with a concave index of 3.04 (which is good overall), with the highest mean value for rural sports policies at the national level. This is followed by the second highest value at the municipal and county levels, and the smallest at the provincial level. Therefore, in the future formulation and implementation of rural sports policies, a multi-dimensional rural sports policy system should be constructed. This would help to strengthen the consistency and effectiveness of the implementation of the policy system and promote the high-quality development of rural sports.